Clustering of ICT human resources capacity in the implementation of E-government in expansion area: a case study from pali regency - Sunda Ariana; Choirul Azim; Darius Antoni (Cogent Business & Management, 2020)
The implementation of E-Government innovation has the ability to help the government reduce costs, enhance quality, save time, and improve the effectiveness and efficiency of the public services. Penukal Abab Lematang Ilir Regency is one of the new expansion areas has been implemented e-government to provide information and public transactions. However, the limited number and low quality of Human Resources in Information and Communication Technology (ICT) department are hampering the success of the innovation. Therefore, this study aims to measure the readiness of ICT human resources in implementing E-Government. This is conducted through the adoption of the Resource-Based View (RBV) to measure and cluster the capacity of ICT human resources based on three indicators which were Technical Capability, Management Capability, and Integrity. Moreover, these indicators are measured using the Gap Analysis method. The results obtained from 120 samples showed the mean striking gap for technical capability under Expertise (3.46) to be 2.65 and management ability under Organization (3.8) to be 2.18 where both were categorized as unprepared. This indicates that Penabal Abab Lematang Ilir District in South Sumatra needs to improve its Technical and Management Capabilities in implementing E-Government.
Keywords: 650; E-government; resource-based view; gap analysis; human resources